(untitled) (Global Journal of Science Frontier Research, 2019)
The Vlasov-Maxwell-Einstein equations are derived from classical action of Lorentz-Schwarzschild-Hilbert-Einstein. We need and get synchronization of times of different particles. On the basis of obtained results we analyze Einstein’s Lambda-term and its connection with dark energy.